Evaluation of Renal Function of Sickle Cell Children in Libreville by Estimating Glomerular Creatinine- Cystatin C Filtration Rate: Renal Function in Sickle Cell Children - Minto’o, Steeve; Loembe, Fifi Claire; Sylvie, Mpira; Nguemou , Nathalie; Djoba Siawaya, Joel; Koko, Jean; Ategbo, Simon J (Journal of Pediatric Nephrology, 2025)
Background and Aim: Sickle cell disease (SCD) is a crucial and growing global health problem. Kidney damage is one of the most common complications of SCD. This study aimed to determine the prevalence of acute kidney injury (AKI) in children with SCD. Methods: This cross-sectional and analytical study was conducted from January 2022 to September 2022. It included children with SCD aged 6 months to 17 years during their steady state. We measured the estimated glomerular filtration rate (eGFR) using the combined creatinine and cystatin C formula for kids (CKiDScr-Cys C). Univariate analyses were performed to measure the relationship between variables and AKI and eGFR, followed by a multivariate analysis using logistic regression. Results: Of the 137 children, 82 (60%) were boys and 55 (40%) were girls. The mean eGFR was 112±45.3 mL/min/1.73 m2. A total of 36 subjects, or 26.3% (95% confidence level [CI], 18.9, 33.6%), had acute AKI. Comparison of characteristics by AKI status showed significant differences in the number of transfusions (P<0.01) and hemoglobin level (P<0.027). eGFR was negatively correlated with the number of transfusions (r=-0.308; 95% CI, -0.477%, -0.117%; P<0.01). Multivariate analysis showed that nutritional status was a protective factor for AKI (P<0.01), and the number of transfusions was a predictive factor of AKI in SCD (P<0.001). Conclusion: The results of our study are an urgent call to implement existing management programs for SCD, from screening to universal access to hydroxyurea, to reduce complications and mortality related to this pathology.